ANÁLISE DA VARIABILIDADE DA FREQUENCIA CARDIACA ESTIMADA A PARTIR DA PRESSÃO SANGUINEA - Oliveira, Fausto Lucena de (2006)
The estimation of heart rate variability (HRV) makes use of the RR intervals obtained from the electrocardiogram (ECG) and prevails as a standard procedure to analyze the modulation regulated by the autonomous nervous system. Moreover, many works have been trying to show that is possible to obtain the HRV from the systolic blood pressure (SBP). Those works often present results of the comparison in the time and frequency domains between the HRV calculated from the RR intervals and the discrete series composed by the maximum values of SBP. However, these comparisons were shown to be reliable only over time domain, for they exhibit disparities on the high frequency bands. In this work we show that the reported disparities on high frequencies could be related to many procedures adopted during the processing of these signals to extract the intervals referred to the cardiac cycles. Here, we use a recent technique called heart instantaneous frequency, proposed to calculate the HRV from both ECG and blood pressure (BP) signals, with the benefit of being more robust to undesired artifacts than the usual peak detectors. Then, we present temporal and spectral results with nonsignificant statistical differences between the HRV extracted from both ECG signals using peak detectors and BP waveforms using the HIF algorithm.